(untitled) - Anderson, Cheryl (Hoboken, N.J, 2007)
This book is not par for the course—hundreds of color photos make learning golf techniques and skills fun. You'll learn how to drive, chip, and putt your way to a respectable score. This visual guide covers basics like grip, stance, and swing, along with techniques for executing various shots and solving common problems. Beginners and veteran duffers will see how to progress from in the rough to on the green. Concise lessons show you all the steps to a skill and are ideal for quick review * Each skill or technique is defined and described * Detailed color photos demonstrate each shot or technique * Step-by-step instructions accompany each photo * Helpful tips provide additional guidance
Keywords: Golf,Môn thể thao chơi gôn; Training,Ðào tạo